Knowledge and attitude regarding standard precautions in a Brazilian public emergency service: a cross-sectional study Conocimiento y actitud sobre las precauciones estándar en un servicio público de emergencia brasileño: un estudio transversal Conhecimento e atitude sobre precauções-padrão em um serviço público de emergência brasileiro: um estudo transversal - Adriana Cristina Oliveira; Maria Helena Palucci Marziale; Maria Henriqueta Rocha Siqueira Paiva; Aline Cristine Souza Lopes (SciELO, 2009)
The purpose of this study was to assess the knowledge and attitude of health care professionals regarding their use of universal precaution measures at a public emergency service. The study also aimed to assess the rates of occupational accidents involving biological substances among those workers. This study was performed with 238 workers, from June to November 2006, using univariate and multivariate analysis. The chance of not adopting precaution measures was 20.7 (95% CI: 5.68 - 75.14) times greater among drivers compared to physicians. No significant association was found between adopting universal precaution measures. The occupational accident rate was 20.6% (40.8% involving sharp-edged objects). The risk of physicians having an occupational accident was 2.7(95% CI: 1.05 - 7.09) times higher than that of drivers. The fact that a staff member had adequate knowledge about universal precaution measures was insufficient to foster compatible attitudes towards reducing the risk of transmitting infectious agents and causing occupational accidents. El estudio tuvo como objetivo evaluar la adopción de medidas de precaución estándar por medio del conocimiento y actitud de los profesionales de un servicio público de emergencia; también evaluar la incidencia de accidentes de trabajo con material biológico entre esos profesionales. La investigación fue realizada con 238 profesionales entre Junio y Noviembre de 2006. Se utilizó el análisis univariado y multivariado. La posibilidad de no adoptar las medidas de precaución fue de 20.7 (95%CI: 5,68 -75,14) veces mayor entre los choferes en comparación con los médicos. No hubo asociación significativa entre la adopción de las medidas de precaución estándar. La incidencia de accidentes de trabajo fue 20.6% (40.8% con material punzo cortante). El riesgo de los médicos de sufrir un accidente de trabajo fue 2.7(95%CI:1.05 - 7.09) veces mayor que los choferes. El hecho de que los miembros del equipo hubiesen presentado un conocimiento adecuado sobre las medidas de precaución estándar fue insuficiente para promover actitudes compatibles para reducir el riesgo de transmisión de agentes infecciosos y accidentes de trabajo. Objetivou-se avaliar a adoção das medidas de precaução padrão por meio de conhecimento e atitude dos profissionais de um serviço público de emergência, assim como a incidência de acidentes de trabalho envolvendo material biológico entre tais profissionais. A pesquisa foi realizada com 238 profissionais entre Junho e Novembro de 2006. Utilizou-se análise univariada e multivariada. A possibilidade de não-adoção das medidas de precaução foi 20.7 (95%CI: 5,68 - 75,14) vezes maior entre motoristas, quando comparados aos médicos. Não houve associação significante entre a adoção às medidas de precaução padrão. A incidência de acidentes de trabalho foi 20.6% (40.8% envolvendo material pérfuro-cortante). O risco de médicos terem um acidente de trabalho foi 2.7(95%CI:1.05 - 7.09) vezes maior que os condutores. O fato de os membros da equipe apresentarem conhecimentos adequados sobre as medidas de precaução padrão foi insuficiente para promover atitudes compatíveis a fim de reduzir o risco de transmissão de agentes infecciosos e acidentes de trabalho.